Developing transversal (soft) competencies in Higher Education Engineering students: the role of the Training Partners in the challenge-based learning model - Ruiz-Cantisani, Maria Ileana; Lara-Prieto, Vianney; García-García, Rebeca; Membrillo-Hernández, Jorge (LACCEI, 2024)
Current education is based on the development of skills that allow students to face an increasingly global and challenging world. One of the most used active learning strategies is Challenge Based Learning (CBL) with the participation of a training partner, which, combined with the educational model, exposes students to real situations that serve as challenges for the development of hard and soft skills necessary for rapid employment integration. In this report, we investigate the role of these training partners in a university institution of higher education that has CBL as its educational model. The training partners studied were companies, and civil or government organizations. We study the role of stakeholders in the development of transversal (soft) and personal competencies in engineering students, using a mixed research methodology, with surveys and interviews, as well as the results of the development of hard skills. The results point to enhance the level of development of soft skills and create an interesting space for reflection by stakeholders for the implementation of solutions to the challenges studied. The soft skills acquired through the interaction with a training partner reinforce those learned in the educational facilities, however the level of development and complexity such as collaborative work, written and oral skills as well as critical thinking, and complex reasoning were clearly higher. But the most appreciated thing is that the involvement of a training partner allows the students to experience a real work environment. A real-life challenge resolution situation. It is important to highlight that the teachers in charge of CBL must have professional preparation to monitor these competencies developed with the training partners.